Bronchopneumonia with measles in Infants and Children at the Department of Child Health School of Medicine, University of North Sumatera/ Dr. Pirngadi Hospital Medan (January 1985 - December 1989) - Charles Hutasoit; Mardiana K. Dj.; Ridwan M. Daulay; Helmi M. Lubis; Zakaria Siregar (Indonesian Pediatric Society, 1991)
A retrospective study was done on patients with bronchopneumonia hospitalized at the Dr. Pirngadi Hospital Medan/School of Medicine, University of North Sumatera; during January 1985 through December 1989. The purpose of this study is to assess the morbidity and mortality of bronchopneumonia with measles and the nutritional status of the patients. Out of the 14.082 patients admitted, 1310 children suffered from bronchopneumonia (10.7%). Ninety nine of them were also with measles (7.6%). Most of the patients with bronchopneumonia without measles were in the age group 0-1 year (58.7%). The mortality waas 24.8% and the highest mortality rate was in the age group of 4-5 years (34.6%). Most of the patients with bronchopneumonia and measles were in the age group of 1-2 years (30.3%). The mortality rate of bronchopneumonia with measles was 22.2% and the highest mortality rate was in the age group of 3-4 years (35. 7%). Bronchopneumonia with or without measles occurred more in malnourished patients rather than in well-nourished cases. All of the patients who had bronchopneumonia with measles in the present study had never been immunized against measles.